Alteration of a motor learning rule under mirror-reversal transformation does not depend on the amplitude of visual error. (May 2015) - Kasuga, Shoko; Kurata, Makiko; Liu, Meigen; Ushiba, Junichi
Highlights: We examined how the error-correction rule was altered under the MR environment. We examined visual error amplitude on the timing when error-correction rule was altered. Error amplitude at a point of rule change decreased when visual gain was decreased. The number of error-increasing trials did not change when visual gain was decreased. Future intensive investigations focusing on the error history were encouraged. Abstract: Human's sophisticated motor learning system paradoxically interferes with motor performance when visual information is mirror-reversed (MR), because normal movement error correction further aggravates the error. This error-increasing mechanism makes performing even a simple reaching task difficult, but is overcome by alterations in the error correction rule during the trials. To isolate factors that trigger learners to change the error correction rule, we manipulated the gain of visual angular errors when participants made arm-reaching movements with mirror-reversed visual feedback, and compared the rule alteration timing between groups with normal or reduced gain. Trial-by-trial changes in the visual angular error was tracked to explain the timing of the change in the error correction rule. Under both gain conditions, visual angular errors increased under the MR transformation, and suddenly decreased after 3–5 trials with increase. The increase became degressive at different amplitude between the two groups, nearly proportional to the visual gain. The findings suggest that the alteration of the error-correction rule is not dependent on the amplitude of visual angular errors, and possibly determined by the number of trials over which the errors increased or statistical property of the environment. The current results encourage future intensive studies focusing on the exact rule-change mechanism.